2017
DOI: 10.1080/16546628.2017.1412792
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran mineral extract increases the expression of anagen-related molecules in human dermal papilla through wnt/catenin pathway

Abstract: The objective of this study is to evaluate of rice bran mineral extract (RBM) increases the expression of anagen-related molecules in human dermal papilla (DOCs). Four treatment groups were established to evaluate the efficacy of RBM, including a negative control, positive control (ascorbic acid), RBM and ortho-silicic acid (Si(OH)4) (OSA) group. Three days after the DPCs were administered the various treatments, western blot analysis showed that type I collagen expression was increased 2.5-fold in the OSA gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Thus, it adds to the strength of the hair and improves hair quality in turn. 19 In the present study, hair thickness (in terms of hair count, unit of hair and average hair) increased after 2 months of administration of ch-OSA ® . A 2007 study reported that oral ch-OSA ® improved tensile strength and produced thicker hair.…”
Section: Discussionsupporting
confidence: 49%
“…Thus, it adds to the strength of the hair and improves hair quality in turn. 19 In the present study, hair thickness (in terms of hair count, unit of hair and average hair) increased after 2 months of administration of ch-OSA ® . A 2007 study reported that oral ch-OSA ® improved tensile strength and produced thicker hair.…”
Section: Discussionsupporting
confidence: 49%
“…The compound markedly reduced catagen entry as compared to control [ 72 ]. Several other plant extracts, such as extracts of polygonum multiflorum [ 73 ], Aconitie ciliare tuber [ 75 ], Thuja orientalis [ 76 ], Malva verticilata [ 77 ], and rice bran extract [ 79 ], have been reported to promote mouse skin hair growth or the proliferation of human DPCs via the activation of β-catenin signaling. Our laboratory has reported that topical application of 3-Deoxysappanchalcone (3-DSC), a bioactive constituent of Caesalpinia sappan L. (Leguminosae), increased the expression of cyclin-dependent kinase-4 (Cdk4), FGF, and vascular VEGF, and promoted anagen phase hair growth in C57BL/6 mice via STST3 activation.…”
Section: Progress In Developing Therapy For Hair Loss By Targetingmentioning
confidence: 99%
“…The research on herbs and active constituents as hair growth promoters has been driven by their less toxicity, easy availability, low‐cost, patient compliance and more than one mode of biochemical action . Specific effects of herbal extracts, polyherbal formulations, flavonoids and natural compounds on DPCs have been examined . In vivo hair growth promoting effects as proof of concept are also mentioned.…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%